Open versus Endoscopic and Microscopic Pituitary Adenoma Excision– An Institutional Experience - Shanmugaiah, Anand; Radhakrishnan, Raghavendran (Nepal Journal of Neuroscience, 2023)
Introduction: For symptomatic nonsecreting pituitary adenomas (PAs), surgical resection remains the treatment of choice. In this retrospective study, we compare the efficacy of open versus endoscopic and microscopic excision of pituitary adenoma, and to evaluate the merits and demerits of each approach. Material and Methods: This study is a retrospective analysis of patients who underwent surgical excision for symptomatic pituitary adenoma in institute of neurosurgery, madras medical college from January 2022 to December 2022. Various parameters were analyzed including the age, sex, type of surgical resection done, duration of surgery, average blood loss, extent of resection of tumors, and intra- and post-operative complication. Results: A total of thirty eight patients with pituitary adenoma were operated from January 2022 to December 2022. Six patients were operated by endonasal endoscopic transsphenoidal surgery and six patients were operated by microscopic transsphenoidal surgery, 26 patients were operated by Pterional craniotomy and excision of tumour. In an endoscopic and microscopic group, complete tumor excision was achieved in 8 patients (66.6%) and in open surgery group, it was achieved in 6 (23.1%) patients. In endoscopic and microscopic group, the mean operative time was 120 ± 25 min (ranged 80–135 min) and in open surgery group, it was 150 ± 15 min (ranged 130–175 min). In endoscopic and microscopic group, mean blood loss was 120 ± 30 ml (80–160 ml), and in open surgery group, it was 200 ± 15 (150–230 ml). Postoperative CSF leak from wound site was present in 1 case in open surgery group. There was no mortality in either group. Duration of hospital stay was 5 days in endoscopic and microscopic group and 14 days for open surgery group. Conclusion: Endoscopic and microscopic approach provides a wide surgical field and broad lateral vision making easier distinction of tumor tissues. Thus, there is less blood loss, less operative time, less postoperative complication, and early discharge from the hospital.